Sob a pele: práticas cutâneas e outras experimentações - Sousa, Jonathan Ferreira de (2023)
In "Under the Skin: cutaneous practices and other experimentations", I present my skin as a support for artistic experimentations based on multidisciplinary practices in contemporary art to incorporate the complexity of the surface of the human body into my creative process in the works presented throughout this research. My interest lies in approaching the multiplicity of the body's envelope using authors such as Georges Bataille, Ashley Montagu and Didier Anzieu. In order to dialogue with my artistic practices, I present some artists who bring the skin to the center of their productions, such as Vera Chaves Barcellos, Orlan, Lygia Clark, Gina Pane, Ariana Page Russell, Rosângela Rennó, John Coplans, among others. In performance, sculpture, text-work and experimentation, I've worked on issues that encompass my skin and the memories present on this surface since my childhood. If the skin is changeable, the research has taken on the same characteristic through a process of perspiration of thought and my artistic practice. Some of the experiments present in this research are: "Pelos Caminhos, Pelos Desvios", "Mão-objeto", "Territórios Cutâneos", "O Rosto que Cai", "Skin.care?". These experiments have been present since the first contact with the research and permeate the whole investigation.